STUDI ISLAM BERBASIS NORMATIVE ISLAMIC AND HISTORICAL ISLAMIC - Ahtar Baihaqi, Wahid; Mulyadi (ASA, 2023)
The development and enrichment of Islamic studies should pay attention to the epistemology carried by the insider-outsider perspective. Epistemologies that have developed in the Islamic world such as al-bayan (rationalism), al-burhan (empiricism) and al-irfan (intuition) must be strengthened with epistemologies that develop with advances in knowledge that are commonly used as a scalpel for outsider analysis such as the phenomenology of religion, distanciation (distancing from the object), appropriation (appropriation of the object for the horizon of the self), ideology criticism (criticism of prejudice and religious illusions), imaginative variation (play of imagination of meaning), deconstruction (demolition of illusions and established doctrines), and hermeneutics (methodology and philosophy of interpretation). With the collaboration of insider and outsider epistemology, the tension between insider and outsider studies can be bridged. Regarding the latter, the idea of an inside-outsider crosscheck, where a scholar's study of a society's religion must be verified by members of that society, deserves to be appreciated.